Becoming more authentic as an elite coach: the case study of Erkka Westerlund - Mallett, C. J.; Bespomoshchnov, V. A.; Arvaja, M.; Rynne, S.; Tiikkaja, J. (International Sport Coaching Journal, 2025)
In this empirical case study, we examine one of Finland`s most successful and respected coaches, Erkka Westerlund. Specifically, we adopted a career-focussed approach that traces his growth as an ice hockey coach through an in-depth understanding of his journey, including his early foray into coaching at 12 years of age, his eventual dismissal as a coach at 42 years of age, his hiatus from coaching, and then his return to national and international honours. The case is comprised of multiple data sources such as semistructured interviews and a raft of secondary sources such as media publications about the participant, his autobiography, and video recordings of him speaking at various conferences and events. Data were analysed through indwelling and reflexive thematic analysis. The pivotal turning point in Erkka Westerlund`s coaching journey was a 6-year sabbatical from coaching (1991-1997). This sabbatical was transformative for him as a person and coach. Specifically, this transformation clarified and aligned his coaching and personal identities, who he was as a person (core values), and the subsequent transformation of his coaching practices that led to national and international success.